The interaction of childhood maltreatment, sex, and borderline personality features in the prediction of the cortisol awakening response in adolescents - Kaess, Michael (Psychopathology, 2017)
Aims: The study aimed to investigate childhood maltreatment, sex, and borderline personality disorder (BPD) symptoms as prospective predictors of adolescent hypothalamic-pituitary-adrenal (HPA) axis reactivity. Method: A sample of 69 adolescents (30 female and 39 male) were selected from a larger longitudinal study of adolescent development and assessed at 3 time points. BPD symptoms were assessed at T1 (approx. 12.5 years), childhood maltreatment was assessed at T2 (approx. 14.9 years), and multiple assessments of salivary cortisol (cortisol awakening response; CAR) were undertaken at T3 (approx. 15.5 years). Results: Multivariate linear regression analysis revealed a significant main effect for childhood maltreatment but not for early BPD symptoms as a predictor of lower CAR in adolescence (p = 0.047). The association between childhood maltreatment and attenuated CAR was moderated by both early BPD symptoms (p = 0.024; no childhood maltreatment-dependent attenuation of CAR in the presence of BPD symptoms) and sex (p = 0.012; childhood maltreatment-dependent attenuation of CAR in females only). Furthermore, a 3-way BPD × childhood maltreatment × sex interaction (p = 0.041) indicated that the moderating effect of BPD symptoms was present in females only. Conclusion: These findings indicate that attenuation of the HPA axis occurs as a response to early maltreatment rather than being related to the early occurrence of BPD pathology. Traumatized female individuals with BPD symptoms might bypass adaptive HPA axis attenuation.